Introduction Prospect of artificial Insemination Technology in Supporting Beef Cattle Development - Elly, Femi H.; Poli, Zulkifli; Kaunang, Charles L.; Lomboan, Agustinus; Salendu, Artise H. S; Ningalo, Rizky (International Journal of Environment, Agriculture and Biotechnology, 2021)
The beef cattle business currently has the prospect to be developed due to the increasing demand for livestock products.The increase in population, economic level and fulfillment of people's nutritional needs had an impact on the tendency of increasing demand and consumption of beef as a source of animal protein.On the other hand, the increase in demand for meat was not matched by availability from beef cattle producers. The problem was that the development of beef cattle in the research area was slow, so the introduction of technology is needed which has an impact on increasing the population of beef cattle.The purpose of this study was to examine the prospects for the introduction of artificial insemination technology. The research method used was a survey method.The sample location was Sangkub District which was determined by purposive sampling, namely as a beef cattle development area. Respondents were beef cattle farmers who have participated in the Artificial Insemination program, as many as 33 people. The data analysis used was descriptive analysis.The prospect of introducing Artificial Insemination at the research location depends on the number of beef cattle, the number of instructors and inseminators, and the response of farmers to the program.The results showed that the beef cattle population in North Bolaang Mongondow Regency from 2018 to 2019 had increased by 7.68 percent.The largest population of beef cattle was in Sangkub District, namely 18.97 percent.The number of instructors in North Bolaang Mongondow Regency were 54 people and inseminators were 6 people. Based on the research results, it can be concluded that Artificial Insemination has the prospect of being introduced even though the success rate was considered sufficient. Suggestions need to increase the socialization of the Artificial Insemination program by the government.